The metropolitan production of “urban” sustainability: Exploring industrial regionalism across the Puget Sound - Pendras, Mark; Dierwechter, Yonn (Frontiers in Sustainable Cities, 2022)
This article engages governance visions for green urbanism and sustainability through the concept of “industrial regionalism”. Bringing together emerging research on the importance of manufacturing to inclusive economies and critiques of “methodological cityism”, we explore the relational production of the iconic “green city” of Seattle. Here we consider how secondary cities, suburbs, and other peripheral spaces get subsumed within the metropolitan production of “urban” sustainability in ways that go unacknowledged and underappreciated. By absorbing tasks of production and social reproduction, such peripheral spaces may enable primate cities like Seattle to claim the mantle of sustainability, highlighting the rain gardens, bike lanes, urban green spaces, and other infrastructures that score high on walkability indices. In contrast, the working-class livelihoods on the periphery are often marginalized from sustainability discourses, if not actively disparaged for their inability to measure up to the green city ideal. This paper aims to offer a corrective by exploring how peripheral spaces are involved in the production of primate city sustainability. Employing the concept of intra-regional relationality, and drawing from census and geospatial data as well as regional planning analyses and reports, we illustrate that “urban” sustainability is produced regionally and relationally. The aim here is to consider how the “industrial region” might gain purchase as an important component of the governance of urban sustainability.